1987
DOI: 10.2307/3345077
|View full text |Cite
|
Sign up to set email alerts
|

Performance Expectancy, Success, Satisfaction, and Attributions as Variables in Band Challenges

Abstract: Motivation of band members was tested by asking them if they had ever challenged for I chair positions and how frequently, if they felt they were correctly placed, what their expected performance level was for 3 months later, what degree of satisfaction and feeling of success they experienced with their current level of performance, and how much they enjoyed playing their instruments. Degree of satisfaction with one's instrument and the factors to which one attributes one's current level of performance were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…The success-capacity attribution and the success-effort attribution predict the academic performance in a positive way, whereas the success-luck attribution does it in a negative way (Barca, Brenlla, Marcos, Morán, & Porto, 2007;Castejón, Navas, Miñano, & Soriano, 2009). In the musical education area, several authors find these same results between the students (Austin & Vispoel, 1998;Chandler, Chiarella, & Auria, 1988;Legette, 1998;Marco, 2010;Painsi & Parncutt, 2004). Marco (2010) confirms that the failure-low capacity attribution influences the academic performance in a negative way.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The success-capacity attribution and the success-effort attribution predict the academic performance in a positive way, whereas the success-luck attribution does it in a negative way (Barca, Brenlla, Marcos, Morán, & Porto, 2007;Castejón, Navas, Miñano, & Soriano, 2009). In the musical education area, several authors find these same results between the students (Austin & Vispoel, 1998;Chandler, Chiarella, & Auria, 1988;Legette, 1998;Marco, 2010;Painsi & Parncutt, 2004). Marco (2010) confirms that the failure-low capacity attribution influences the academic performance in a negative way.…”
Section: Introductionsupporting
confidence: 58%
“…La atribución del éxito a la capacidad o al esfuerzo predice positivamente el rendimiento académico, contrariamente a la atribución a la suerte, que lo hace negativamente (Barca, Brenlla, Marcos, Morán, y Porto, 2007;Castejón, Navas, Miñano, y Soriano, 2009). En el campo de la educación musical, varios autores encuentran estos mismos resultados entre los estudiantes (Austin y Vispoel, 1998;Chandler, Chiarella, y Auria, 1988;Legette, 1998;Marco, 2010;Painsi y Parncutt, 2004). Marco (2010) comprueba que la atribución del fracaso a la baja capacidad influye negativamente sobre el rendimiento académico.…”
Section: Introductionunclassified
“…For example, while personal desire has been identified as an important reason for starting to learn an instrument (MacKenzie, 1991), context-oriented feelings of satisfaction are important for continued motivation and engagement (Rife, Shnek, Lauby, & Lapidus, 2001;Schmidt, 2005). Chandler, Chiarella and Auria (1988) identified a similar relationship in the context of instrumental practice. From a more general psychological perspective, positive experience of an activity is a pre-requisite for future re-engagement (e.g., Hagger et al, 2009;Kukla, 1978).…”
mentioning
confidence: 86%
“…This has also been the case in music (for a review see Asmus, 1994). Chandler, Chiarella and Auria (1988) found that music students who reported that they would choose to continue to play their instrument were more satis ed with their current level of performance, enjoyed playing more, believed that technical knowledge was an important in uence on performance, practised more, expected to play the instrument longer, aspired to promotion within their musical group, generally Downloaded by [Dalhousie University] at 08:01 01 October 2012 attributed success to ability not luck, regarded personal effort as important, valued help from their teacher, and believed that it was valuable and important to play an instrument.…”
Section: The Characteristics Of the Individual Learnermentioning
confidence: 97%